2010
DOI: 10.1016/j.nurt.2010.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Astrocytes for Stroke Therapy

Abstract: Summary: Stroke remains a major health problem and is a leading cause of death and disability. Past research and neurotherapeutic clinical trials have targeted the molecular mechanisms of neuronal cell death during stroke, but this approach has uniformly failed to reduce stroke-induced damage or to improve functional recovery. Beyond the intrinsic molecular mechanisms inducing neuronal death during ischemia, survival and function of astrocytes is absolutely required for neuronal survival and for functional rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
108
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(116 citation statements)
references
References 153 publications
(192 reference statements)
4
108
0
Order By: Relevance
“…It is generally acknowledged that astrocytes are substantially more ischemia‐resistant than neurons and survive in conditions of limited blood supply, characteristic for penumbra surrounding the core of the ischemic infarction (Swanson, Farrell, & Stein, 1997; Vangeison, Carr, Federoff, & Rempe, 2008). These surviving astrocytes undergo activation and are involved in neuroprotection and post‐ischemic regeneration (Takano, Oberheim, Cotrina, & Nedergaard, 2009; Zhao and Rempe 2010). Astroglia contributions to brain resilience could include clearance of glutamate, control over K + concentration, supply of lactate to the stressed neurons, secretion of neuroprotective factors, and scavenging reactive oxygen species by releasing GSH and ascorbic acid (Liu and Chopp 2015; Zhao and Rempe 2010).…”
Section: Astrocytes In the Diseased Brain Are Central To Neuropathologymentioning
confidence: 99%
See 2 more Smart Citations
“…It is generally acknowledged that astrocytes are substantially more ischemia‐resistant than neurons and survive in conditions of limited blood supply, characteristic for penumbra surrounding the core of the ischemic infarction (Swanson, Farrell, & Stein, 1997; Vangeison, Carr, Federoff, & Rempe, 2008). These surviving astrocytes undergo activation and are involved in neuroprotection and post‐ischemic regeneration (Takano, Oberheim, Cotrina, & Nedergaard, 2009; Zhao and Rempe 2010). Astroglia contributions to brain resilience could include clearance of glutamate, control over K + concentration, supply of lactate to the stressed neurons, secretion of neuroprotective factors, and scavenging reactive oxygen species by releasing GSH and ascorbic acid (Liu and Chopp 2015; Zhao and Rempe 2010).…”
Section: Astrocytes In the Diseased Brain Are Central To Neuropathologymentioning
confidence: 99%
“…These surviving astrocytes undergo activation and are involved in neuroprotection and post‐ischemic regeneration (Takano, Oberheim, Cotrina, & Nedergaard, 2009; Zhao and Rempe 2010). Astroglia contributions to brain resilience could include clearance of glutamate, control over K + concentration, supply of lactate to the stressed neurons, secretion of neuroprotective factors, and scavenging reactive oxygen species by releasing GSH and ascorbic acid (Liu and Chopp 2015; Zhao and Rempe 2010). Recently, using optogenetic control of H + pumps expressed on astrocytes, it was demonstrated that alkalinisation of astrocytes could reduce glutamate release and limit the ischemic brain damage in a cerebellar ischemia model.…”
Section: Astrocytes In the Diseased Brain Are Central To Neuropathologymentioning
confidence: 99%
See 1 more Smart Citation
“…These can directly stimulate aspects of neural repair [27], and also induce an activated state in brain endothelial cells and astrocytes. Activated astrocytes and endothelial cells then further produce molecules that induce or alter the brain's reparative response [19,28]. Several cytokines from these cells influence a stem cell response to stroke.…”
Section: Radial Stroke: Triggers For Neural Repairmentioning
confidence: 99%
“…Recent evidence points to astrocytes as an alternative candidate for the development of novel stroke therapies. 1 Astrocytes are the most abundant cell type in the human brain and they are more resistant to ischemia than neighboring neurons. They naturally support neuronal survival and modulate neuronal recovery by providing metabolic and trophic support, glutamate and K þ clearance, as well as antioxidant protection during ischemia.…”
Section: Introductionmentioning
confidence: 99%